2016
DOI: 10.1152/ajpgi.00369.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role of epithelial ion transports in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with a complex pathogenesis. Diarrhea is a highly prevalent and often debilitating symptom of IBD patients that results, at least in part, from an intestinal hydroelectrolytic imbalance. Evidence suggests that reduced electrolyte absorption is more relevant than increased secretion to this disequilibrium. This systematic review analyses and integrates the current evidence on the roles of epithelial Na+-K+-ATPase (NKA), Na+/H+ exchangers (NHEs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 155 publications
(150 reference statements)
1
33
0
Order By: Relevance
“…These results indicate that PGE 2 may act as a robust and direct mediator of anion/fluid secretion from IECs, which cannot be affected by other pro-inflammatory cytokines. Additionally, the results raise the possibility that the local levels of PGE 2 may constitute one of the components in the pathophysiology of IBD-associated diarrhoea4243.…”
Section: Resultsmentioning
confidence: 93%
“…These results indicate that PGE 2 may act as a robust and direct mediator of anion/fluid secretion from IECs, which cannot be affected by other pro-inflammatory cytokines. Additionally, the results raise the possibility that the local levels of PGE 2 may constitute one of the components in the pathophysiology of IBD-associated diarrhoea4243.…”
Section: Resultsmentioning
confidence: 93%
“…Recent evaluation of the NHE3 inhibitor tenapanor in a Phase 3 clinical trial for IBS-C showed limited efficacy, with 27% combined pain and stool pattern response rate for the treated group versus 18.7% for placebo (30). NHE3 is expressed in the small intestine and proximal colon, but not in distal colon (12,32). The limited clinical efficacy of NHE3 inhibition for constipation might be due to unimpaired downstream fluid absorption in the distal colon.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focused on Na + -H + -exchangers (NHE). However, despite their ability to indirectly influence sodium transport through Na + ,K + -ATPase (NKA) activity or electrical gradient, K + channels (KC) have been seldom explored in IBD yet [15]. Therefore, we intended to study 1) the effects of PRR activation on the MP of IEC and 2) the importance of KC on this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, their contribution to IBD-associated diarrhea through indirect regulation of sodium absorption in IECs has been scarcely addressed [15]. Therefore, we intended to study the impact of PRR activation on KC activity in the human intestinal HT-29 cells.…”
Section: Introductionmentioning
confidence: 99%